The Effect of Context Clues Mastery on Students' Reading Comprehension of Procedure Text (A study at the Eleventh Grade Students of SMA Negeri 5 Padangsidimpuan) - siti wartini harahap (JURNAL LINER (Language Intelligence and Educational Research), 2018)
The objectives of the research are to find out: 1) the extent of the application of context clues mastery, 2) the extent of students’ reading comprehension of procedure text before and after using context clues mastery, 3) whether there is any significant effect of context clues mastery on students’ reading comprehension of procedure text at the eleventh grade students of SMA Negeri 5 Padangsidimpuan. This research uses experimental method. The population is all the eleventh grade which are divided into six classes and total are 178 students. The sample consists of 31 students by using cluster sampling. The technique of collecting data is used observation and test. After collecting the data, the mean of application description of context clues mastery is 3.60. It is categorized “Very Good”. The students’ reading comprehension of procedure text before using context clues mastery is 73.23. It is categorized “Good”. The students’ reading comprehension of procedure text after using context clues mastery is 85.81. It is categorized “Very Good”. The calculation of ttest formula is 7.82, and ttable is 2.04. It means that there is a significant effect of context clues mastery on students’ reading comprehension of procedure text at the eleventh grade students of SMA Negeri 5 Padangsidimpuan. Keywords: Context Clues, Reading Comprehension, Procedure Text.